DEVELOPMENT OF NEW DESIGN AND MATHEMATICAL MODELING OF HEAT AND MASS TRANSFER HEAT EXCHANGER VENTILATION SYSTEMS ЩА ENERGY HOUSES - Gorobetz, V.; Masuk, M. (Energy and Automation, 2016)
The new design of compact heat exchanger tube placement tube bundle used in building energy for saving ventilation system to cooland heating the outside air using the underground water wells is proposed. A mathematical modeling of mass and heat transfer to the new design of the heat exchanger is developed. As a result of numerical modeling of hydrodynamic and thermal processes using CAD software ANSYS Fluent 14.0 received distributions of velocity, pressure and temperature in the channels and tube heat exchanger. Comparison of characteristics of new designs of heat exchangers and famous designs is conducted.